2014
DOI: 10.1186/alzrt262
|View full text |Cite
|
Sign up to set email alerts
|

β-amyloid deposition is shifted to the vasculature and memory impairment is exacerbated when hyperhomocysteinemia is induced in APP/PS1 transgenic mice

Abstract: IntroductionVascular dementia is the second most common cause of dementia after Alzheimer’s disease (AD). In addition, it is estimated that almost half of all AD patients have significant cerebrovascular disease comorbid with their AD pathology. We hypothesized that cerebrovascular disease significantly impacts AD pathological progression.MethodsWe used a dietary model of cerebrovascular disease that relies on the induction of hyperhomocysteinemia (HHcy). HHcy is a significant clinical risk factor for stroke, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 40 publications
6
47
1
Order By: Relevance
“…Mice with 6-12 months of age exhibit significant elevations in plasma homocysteine levels in both WT and APP/PS1 mice when fed this diet (Sudduth et al 2013). Sudduth et al (2014) found in APP/PS1 mice with moderate HHcy, HHcy did not affect Ab levels, but deposition of amyloid was more associated with the vasculature. In the frontal cortex and hippocampus, there was a 50-60 % reduction in parenchymal amyloid and over double the amount of CAA in HHcy APP/PS1 mice relative to control APP/PS1 mice.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Mice with 6-12 months of age exhibit significant elevations in plasma homocysteine levels in both WT and APP/PS1 mice when fed this diet (Sudduth et al 2013). Sudduth et al (2014) found in APP/PS1 mice with moderate HHcy, HHcy did not affect Ab levels, but deposition of amyloid was more associated with the vasculature. In the frontal cortex and hippocampus, there was a 50-60 % reduction in parenchymal amyloid and over double the amount of CAA in HHcy APP/PS1 mice relative to control APP/PS1 mice.…”
Section: Introductionmentioning
confidence: 94%
“…Severe suppression of microglia by high methionine intake is associated with a very mild HHcy compared to a modest suppression of microglia by B-vitamin deficiency associated with a severe HHcy (Troen et al 2007). Mice with moderate HHcy displayed significant induction of microhemorrhages and a neuroinflammatory phenotype switch from a repair-like state to a pro-inflammatory state in both WT and APP/PS1 mice (Sudduth et al 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(Hooijmans, et al, 2007). A similar ratio of parenchymal to vascular associated amyloid is seen in this mouse at 12 months of age (Sudduth, et al, 2014). A photo micograph of a 205…”
Section: Methodsmentioning
confidence: 56%
“…Several models linking the b-amyloid hypothesis of AD and cerebral vascular pathology have been proposed (van Norden et al, 2012). On one hand, vascular pathology affects the age of onset of cognitive impairment and dementia in AD (de la Torre, 2004) likely due, at least in part, to altered b-amyloid clearance (ElAli et al, 2013;Sudduth et al, 2014). On the other hand, b-amyloid deposition in blood vessels produces secondary vascular lesions (van Norden et al, 2012).…”
Section: Mixed Forms Of Dementiamentioning
confidence: 97%